Synthesis and Characterization of Novel Oxime Prodrug of Gliclizide - Vijayaraj1, S.; Anitha2, S.; Omshanthi2, B.; Sampath Kumar3, K.P. (Asian Journal of Chemistry, 2014)
Diabetes has emerged as a major healthcare problem throughout the world. Gliclizide is a widely used sulphonyl urea compound to treat diabetes. Gliclizide is categorized under biopharmaceutical classification system class II drug which do have poor solubility. Drug molecules with limited aqueous solubility are becoming increasingly prevalent in the research and development portfolios of discovery focused pharmaceutical companies. Prodrugs are an established concept to overcome barriers like poor solubility. Aqueous solubility is an important parameter to enhance the bioavailability of drug. Hence the present study aims to enhance aqueous solubility and in turn bioavailability by synthesis of novel oxime prodrug of gliclizide. The prepared prodrug was characterized by IR, NMR, Mass and DSC. in vitro chemical hydrolysis profiles revealed that the synthesized oxime derivatives of gliclizide are chemically stable in simulated gastric fluid pH 1.2. Decrease in log P value indicates the increase in hydrophilic property of synthesized oxime derivatives of gliclizide.